'The Queering of Architecture History Has Yet to Happen': The Intra-Canonical Outlook of Beatriz Colomina. Issue 1 (10th December 2020) - Kotsioris, Evangelos
Abstract : In this interview, Beatriz Colomina revisits her formative years as an architect and architectural historian, from Barcelona to New York, and from her foundational writings on Privacy and Publicity (1994a ) to her recent book, X-Ray Architecture (2019 ). Retracing the links between Marxism, feminism, theory, pedagogy, media, and modernity, Colomina recounts to Evangelos Kotsioris her seminal approach of modern architecture as media and her research in Le Corbusier's archive. She refers to the social networks of her years in Barcelona and New York that contributed to the development of her working approach. Adopting a tone that is partly autobiographical and partly analytical, she discusses the pleasures and challenges of working with archival texts and images, and the links between the practices of architecture and history writing. For the first time she recounts in detail her student years under Franco's regime in Spain, her experience of New York during the AIDS epidemic, and her contacts with the feminist circles of the 1990s, among others. Such ties echo the development of the field beyond Colomina's individual contribution to it, and they lead to broader reflections about the state and challenges of architectural historiography today.